Development and validation of emission model for a petrol engine using response surface methodology (RSM) - Saidur, Rahman; Leong, W.B.; Masjuki, Haji Hassan; Jahirul, I.; Tamjis, M.R. (Journal - The Institution of Engineers, Malaysia, 2005)
Hydrocarbon emissions are generated from the presence of unburned fuel in the exhaust of a petrol engine. Liquid fuels contain 10 to 20 major species of hydrocarbon and some 100 to 200 minor species. Most of these species are found in the exhaust gas of a petrol engine. However, some of the exhaust hydrocarbons are not found in the parent fuel, but are hydrocarbons derived from the fuel whose structure was altered within the cylinder by incomplete chemical reaction. About 50 of the total hydrocarbons are emitted in this way. In this paper a mathematical model utilising the response surface methodology (RSM) has been developed for predicting the hydrocarbon (HC) emission from a petrol engine. The adequacy of the model has been investigated statistically by the analysis of variance (ANOVA) as well. Based on the response models, contours have been plotted in throttle-speed planes. For a given surface, these contours help to predict the setting parameters for minimum hydrocarbon emission.